Answer:
The object accelerates downward at 4 m/s² since the tension on the rope is less than weight of the object.
Explanation:
Given;
mass of the object, m = 2 kg
weigh of the object, W = 20 N
tension on the rope, T = 12 N
The acceleration of the object is calculated by applying Newton's second law of motion as follows;
T = F + W
T = ma + W
ma = T - W
(the negative sign indicates deceleration of the object)
The object accelerates downward at 4 m/s² since the tension on the rope is less than weight of the object.
Answer:
The pressure of the remaining gas in the tank is 6.4 atm.
Explanation:
Given that,
Temperature T = 13+273=286 K
Pressure = 10.0 atm
We need to calculate the pressure of the remaining gas
Using equation of ideal gas
![PV=nRT](https://tex.z-dn.net/?f=PV%3DnRT)
For a gas
![P_{1}V_{1}=nRT_{1}](https://tex.z-dn.net/?f=P_%7B1%7DV_%7B1%7D%3DnRT_%7B1%7D)
Where, P = pressure
V = volume
T = temperature
Put the value in the equation
....(I)
When the temperature of the gas is increased
Then,
....(II)
Divided equation (I) by equation (II)
![\dfrac{P_{1}V}{P_{2}V}=\dfrac{nRT_{1}}{\dfrac{n}{2}RT_{2}}](https://tex.z-dn.net/?f=%5Cdfrac%7BP_%7B1%7DV%7D%7BP_%7B2%7DV%7D%3D%5Cdfrac%7BnRT_%7B1%7D%7D%7B%5Cdfrac%7Bn%7D%7B2%7DRT_%7B2%7D%7D)
![\dfrac{10\times V}{P_{2}V}=\dfrac{nR\times286}{\dfrac{n}{2}R368}](https://tex.z-dn.net/?f=%5Cdfrac%7B10%5Ctimes%20V%7D%7BP_%7B2%7DV%7D%3D%5Cdfrac%7BnR%5Ctimes286%7D%7B%5Cdfrac%7Bn%7D%7B2%7DR368%7D)
![P_{2}=\dfrac{10\times368}{2\times286}](https://tex.z-dn.net/?f=P_%7B2%7D%3D%5Cdfrac%7B10%5Ctimes368%7D%7B2%5Ctimes286%7D)
![P_{2}= 6.433\ atm](https://tex.z-dn.net/?f=P_%7B2%7D%3D%206.433%5C%20atm)
![P_{2}=6.4\ atm](https://tex.z-dn.net/?f=P_%7B2%7D%3D6.4%5C%20atm)
Hence, The pressure of the remaining gas in the tank is 6.4 atm.
A) 0.189 N
The weight of the person on the asteroid is equal to the gravitational force exerted by the asteroid on the person, at a location on the surface of the asteroid:
![F=\frac{GMm}{R^2}](https://tex.z-dn.net/?f=F%3D%5Cfrac%7BGMm%7D%7BR%5E2%7D)
where
G is the gravitational constant
8.7×10^13 kg is the mass of the asteroid
m = 130 kg is the mass of the man
R = 2.0 km = 2000 m is the radius of the asteroid
Substituting into the equation, we find
![F=\frac{(6.67\cdot 10^{-11})(8.7\cdot 10^{13} kg)(130 kg)}{(2000 m)^2}0.189 N=](https://tex.z-dn.net/?f=F%3D%5Cfrac%7B%286.67%5Ccdot%2010%5E%7B-11%7D%29%288.7%5Ccdot%2010%5E%7B13%7D%20kg%29%28130%20kg%29%7D%7B%282000%20m%29%5E2%7D0.189%20N%3D)
B) 2.41 m/s
In order to orbit just above the surface of the asteroid (r=R), the centripetal force that keeps the astronaut in orbit must be equal to the gravitational force acting on the astronaut:
![\frac{GMm}{R^2}=\frac{mv^2}{R}](https://tex.z-dn.net/?f=%5Cfrac%7BGMm%7D%7BR%5E2%7D%3D%5Cfrac%7Bmv%5E2%7D%7BR%7D)
where
v is the speed of the astronaut
Solving the formula for v, we find the minimum speed at which the astronaut should launch himself and then orbit the asteroid just above the surface:
![v=\sqrt{\frac{2GM}{R}}=\sqrt{\frac{2(6.67\cdot 10^{-11})(8.7\cdot 10^{13} kg)}{2000 m}}=2.41 m/s](https://tex.z-dn.net/?f=v%3D%5Csqrt%7B%5Cfrac%7B2GM%7D%7BR%7D%7D%3D%5Csqrt%7B%5Cfrac%7B2%286.67%5Ccdot%2010%5E%7B-11%7D%29%288.7%5Ccdot%2010%5E%7B13%7D%20kg%29%7D%7B2000%20m%7D%7D%3D2.41%20m%2Fs)
Answer:
3.67 km
Explanation:
Joe distance towards coffee shop is,
![OB=0.40 km](https://tex.z-dn.net/?f=OB%3D0.40%20km)
And the Max distance towards bookstore is,
![OA=3.65 km](https://tex.z-dn.net/?f=OA%3D3.65%20km)
Now the distance between the Joy and Max will be,
By applying pythagorus theorem,
![AB=\sqrt{OB^{2}+OA^{2}}](https://tex.z-dn.net/?f=AB%3D%5Csqrt%7BOB%5E%7B2%7D%2BOA%5E%7B2%7D%7D)
Substitute 0.40 km for OB and 3.65 km for OA in the above equation.
![AB=\sqrt{0.40^{2}+3.65^{2}}\\AB=\sqrt{13.4825} \\AB=3.67 km](https://tex.z-dn.net/?f=AB%3D%5Csqrt%7B0.40%5E%7B2%7D%2B3.65%5E%7B2%7D%7D%5C%5CAB%3D%5Csqrt%7B13.4825%7D%20%5C%5CAB%3D3.67%20km)
Therefore the distance between there destination is 3.67 km.
Answer:
The force when θ = 33° is 1.7625 times of the force when θ = 18°
Explanation:
The force on a moving charge through a magnetic field is given by
F = qvB sin θ
q = charge of the moving particle
v = Velocity of the moving charge
B = Magnetic field strength
θ = angle between the magnetic field and the velocity (direction of the motion) of the moving charge
Because qvB are all constant, we can call the expression K.
F = K sinθ
when θ = 18°,
F = K sin 18° = 0.309K
when θ = 33°, let the force be F₁
F₁ = K sin 33° = 0.5446K
(F₁/F) = (0.5446K/0.309K) = 1.7625
F₁ = 1.7625 F
Hope this Helps!!!